COMPARISON USAGE TIME OF LED Light Curing Unit TO NANOFILLER COMPOSIT RESIN TOWARDS ITS COMPRESSIVE STRENGTH - Diana, Sherli; Gunawan Halim, Novia; Erlita, Isyana (FKG Unlam, 2017)
Background: A perfect polymerization is very important for good restoration. Good restoration is affectedby some factors. One of it is LED Light Curing Unitâs usage time. LED Light Curing Unitâs usage in which morethan five years ideal lifetime causes decreasing light intensity and compressive strength of composite resins.Purpose: To analyze the compressive strength value of nanofilled composite resins that polymerized with a new(never been used) and used LED Light Curing Unitâs. Methods: Laboratory experimental method (trueexperimental) with post-test only with control group design. First group with 16 samples as positive controlpolymerisez with new and (never been used) LED Light Curing Unit. The second group with 16 samplespolymerized with LED Light Curing Unit that has been used more than five years. Sample were molded with4mm diameter and 8mm thick. The compressive strength value is measured with Universal Testing Machine.Results: Independent T-Test showed p=0,000 (p<0,05), that means there was significant differences oncompressive strengthâs value of nanofilled composite resins that polymerised based on Light Curing Unitâsusage time. Compressive strength value of nanofilled composite resins polymerised by LED Light Curing Unitthat has been used more than five years was lower than new and never been used LED Light Curing Unit. UsedLED Light Curing Unit has decreasing light intensity outcome, so the photons that achieve the restoration isreduced and cause imperfect polymerization. Conclusion: Compressive strength value of nanofilled compositeresins polymerised by LED Light Curing Unit that has been used more than five years was lower than nanofilledcomposite resins polymerised by new and never been used LED Light Curing Unit.